Education on Hypertension Prevention in The Elderly - Firman Prastiwi; Noor Fitriyani; Amin Aji Budiman; Muhamad Nur Rahmad (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2023)
ABSTRACT Elderly people generally experience various kinds of changes that have an impact on the incidence of hypertension. Hypertension is still a disease that dominates the elderly and is a major risk factor for cardiovascular disease, stroke and kidney failure. A more common cause related to hypertension is the lack of knowledge of the elderly themselves about hypertension. The aim of this community service is to provide education on preventing hypertension in the elderly. The community service theme was Education on Handling Hypertension in the Elderly which was held on December 23 2022 at the WCS Mental Revolution House and was attended by 32 elderly people. The activity was carried out by delivering hypertension prevention material using leaflets and powerpoints, followed by discussions and questions and answers. From the results of an assessment of elderly people's knowledge about treating hypertension before being given education (pretest), most of them were poor, 10 people (31.3%). After being given education using leaflets and power points (posttest), the level of knowledge of the elderly regarding hypertension management was mostly good, 18 people (56.3%). The results of the Marginal Homogeneity Test analysis obtained a value of 0.005, indicating that there is an influence of education on hypertension management on the knowledge of the elderly. Providing education using leaflets and powerpoint media can increase the knowledge of the elderly Keywords : Health Education, Hypertension, Elderly